Peripheral Arterial Aneurysms in the Behçet's disease - Rodríguez Goñi, Pablo; Fleitas, Gabriela; González, Jorge (Cirugía del Uruguay, 2004)
Clinical review of a patient suffering from Behqet's disease complicated by peripheral arterial aneurysm. Behqet's disease is an autoimmune vasculitis diagnosed by clinical procedures, which may affect the mucosae, skin, central nervous system and b/ood vesse/s. In this case it started by aneurisms in the right femoral artery and /eft carotid bifurcation. Both were treated surgical/y with good evo/ution. This pathology is very rare and ear/y diagnosis is important in preventing complications, particular/y those that are vascular